Practical reasoning in a social world : how we act together - Graham, Keith, 1945- (Cambridge University Press, 2002)
Keith Graham examines the philosophical assumptions behind the ideas of group membership and loyalty. He offers a new understanding of the multiplicity of sources which vie for the attention of human beings as they decide how to act, and challenges the conventional division between self-interest and altruism.